A comprehensive approach for biorefineries design based on experimental data, conceptual and optimization methodologies: The orange peel waste case. (April 2021) - Mariana, Ortiz-Sanchez; Camilo, Solarte-Toro Juan; Ariel, Cardona-Alzate Carlos
Highlights: A comprehensive methodological approach is proposed to design biorefineries. The methodology was applied to determine an optimal biorefinery to upgrade OPW. The results of the methodology give a more contextualized biorefinery process. Abstract: The aim of this work was to propose a comprehensive methodological approach integrating two of the most applied approaches to design biorefineries based on experimental data: conceptual design and optimization. The proposed methodology involves three critical aspects i) experimental procedures, ii) simulation approach, and iii) optimization tools. The proposed approach was applied to a specific case as an example. The orange peel waste (OPW) was studied as raw material to feed the biorefinery with the purpose of valorizing the residues produced by the orange juice factories in the Colombian context. After implementing the methodology, the results show how essential oil and biogas were the most profitable and reliable products to be obtained through the processing of OPW. In this case, it is demonstrated also, that the understanding of the biorefinery possibilities is higher when this design methodology is applied.